1982
DOI: 10.1111/j.1600-0676.1982.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of polyunsaturated phosphatidyl choline in HBsAg negative chronic active hepatitis: results of prospective double‐blind controlled trial

Abstract: ABSTRACT— In a prospective double‐blind trial, polyunsaturated phosphatidyl choline therapy (3 g/day) was given in addition to normal maintenance immunosuppressive therapy to 15 patients with HBsAg negative chronic active hepatitis. Histological evidence of disease activity was significantly reduced in the phospholipid‐treated group. The results indicate that polyunsaturated phosphatidyl choline is of value as additional treatment in the management of patients with HBsAg negative chronic active hepatitis whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Some studies showed an amelioration of hepatic symptoms and an enhancement of liver functions with soybean PC supplementation in patients presenting non alcoholic liver damage [102,107]. Moreover, soybean PC (Essentiale ® , see table 2) was given to patients presenting dramatic circulatory problems and simultaneous hepatic disorders, resulting in enhancement of hemodynamics, intrahepatic cholestasis, liver function and in the general lipid metabolism [108].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed an amelioration of hepatic symptoms and an enhancement of liver functions with soybean PC supplementation in patients presenting non alcoholic liver damage [102,107]. Moreover, soybean PC (Essentiale ® , see table 2) was given to patients presenting dramatic circulatory problems and simultaneous hepatic disorders, resulting in enhancement of hemodynamics, intrahepatic cholestasis, liver function and in the general lipid metabolism [108].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PPC promotes liver cell regeneration, and improves lipid metabolism in the blood and liver. Thus, PPC can be applied to the treatment of various acute and chronic liver diseases . Recently, PPC has gained recognition, resulting in increased availability of commercial preparations.…”
Section: Introductionmentioning
confidence: 99%
“…One study, phase IIA, double blind, randomized, placebo controlled study including 60 patients with chronic active, non-steroid dependent, ulcerative colitis, showed that 6 g of retarded release phosphatidylcholine rich PL during three months period alleviates inflammatory activity that is caused by ulcerative colitis [50]. Another study showed that polyunsaturated PC is beneficial supplementary treatment for patient management in HBsAg negative chronic active hepatitis, where the condition is inefficiently controlled with standard doses of immunosuppressive therapy [51]. Dietary PC was also shown to alleviate the orotic acid-induced fatty liver in rats OA-, mostly through the reduction of TG synthesis in the liver and improvement of FA β-oxidation [52].…”
Section: Phospholipids (Pl)mentioning
confidence: 99%